Grain boundary fracture and plasticity in Sigma=25 bicrystals of silicon - Jacques, A; Roberts, S (1996)
Grain boundary fracture was investigated in Si Sigma=25 bicrystalline 4 point bend specimens stressed under a constant load at 550 and 600 degrees C. Dislocation sources were placed near the GB. Specimens loaded to stresses higher than 310 MPa always fractured at the GB soon after the first dislocation arrived at the boundary. At lower applied loads, dislocation transmission through the GB was observed, and fracture, if it occurred, was much delayed.